Investigation into surface texturing by magnetic field assisted laser-produced plasma - Hamid Farrokhi (2013)
In this thesis, we investigated the irradiation of silicon with infrared fiber laser (λ = 1090 nm) at energy densities exceeding the ablation threshold. We characterize the irradiated surface and properties of the ejected material showing the big volume of silicon oxide at the rim of the irradiated line. The results showed that the infrared fiber laser could not be regarded as a suitable tool for the purpose of micromachining and effective ablation of silicon. Seeking for reason revealed that silicon is highly transparent to the infrared wavelength of fiber laser (λ=1090 nm). Thus it was proposed to make use of the laser to texture silicon surface rather than to ablate it. Since surface texturing is an important research area in the field of laser material processing with a broad range of applications, thus we investigated silicon surface texturing using infrared fiber laser in a background gas. Micron and submicron texturing of silicon by laser ablation is of great interest due to its wide use in microelectronics and solar cells. However, the approaches are based on the target ablation and redistribution of melt materials. Hardly any reports can be found in the public domain on the use of non-ablative laser surface texturing to form uniform patterns. As it is said earlier silicon is known to be highly transparent to the infrared wavelength of fiber laser (λ=1090 nm), so fiber laser is not regarded as a suitable tool for ablative texturing of silicon. Thus we developed a technique to irradiate and pattern silicon surface in O2 gas environment using various laser parameters (laser power and beam dwell time). With this technique, we succeeded in patterning Si surface by non-ablative laser texturing using continuous wave fiber laser (λ=1090 nm). We explained the non-ablative surface texturing in terms of laser-induced localized thermal oxidation. However, the proposed mechanism is based on qualitative analyses only. Thus we have chosen finite element method for thermal modeling of phenomenon in order to understand the mechanism of non-ablative texturing. The analysis shows the technique is based on laser-induced thermal oxidation. The numerical analysis was used to map laser parameters (laser power vs dwell time) for non-ablative laser texturing of silicon. It shows the effective oxidation zone to produce regular bumps on silicon. Since non-ablative laser surface texturing could be based on thermal or non-thermal mechanism and it has not been well studied, we investigated non-ablative Si surface texturing based on laser induced non-thermal oxidation phenomenon as a new technique of surface structuring. We used low repetition rate (1 kHz) of femtosecond laser pulses with negligible thermal accumulation and succeeded in non-ablative direct writing of silicon surface. The approach is shown to be based on laser-induced localized non-thermal oxidation of silicon that will be explained in details. Finally we have investigated and developed magnetic field assisted laser ablation as a novel technique of surface structuring. The use of a magnetic field with laser produced plasma (LPP) is of great interest in basic and engineering research since a magnetic field can effectively control the dynamic properties of this transient and energetic plasma. In engineering research, most studies have been conducted on pulsed laser deposition (PLD) techniques to get the particulate-free films. Some researchers have also investigated magnetic field assisted laser welding and hardening to increase penetration depth, to unify elements distribution and to favor pore outgassing. However, hardly any studies can be found in the public domain on magnetic field assisted laser micromachining of materials and its effect on laser ablation efficiency. In the present study, we have studied the magnetic field-assisted laser ablation of materials irradiated by nanosecond (355nm, 20ns) and femtosecond (775 nm, 150 fs) lasers. Silicon has been initially chosen for the study since it is an important semiconductor material in electronic, solar cells, and sensors. Stainless steel 304 and titanium alloy (Ti4Al6V) were also chosen to examine applicability of the technique in surface structuring of various materials. The solenoid copper coil was designed and fabricated to apply an axial magnetic field (B to target plane and ∥ to laser beam) with various field strength. The results showed the remarkable effect of the external magnetic field on the ablation efficiency. However, laser ablation efficiency under the magnetic field in ns laser is much great comparing with that in femtosecond laser ablation. This might be due to no laser-plasma interactions in the fs irradiation. The plasma cools quickly since no further energy is supplied by the fs laser. However, a fraction of the laser energy is absorbed by the ns-induced plasma that results in greater temperature and electron density of the plasma. Magnetohydrodynamic (MHD) analysis showed that the magnetic field confines the induced plasma. The ns-induced plasma, which is denser and hotter comparing with the fs-induced plasma, becomes denser and hotter under the external magnetic field. This leads to efficient deposition of plasma thermal energy and high laser ablation efficiency in ns laser ablation, as shown in the results. It is expected that this technique would have potential applications in the laser processing of hard-to-ablate materials, laser cutting, laser welding, etc. In this thesis, we hope to give the reader an impression of the exciting field of non-ablative laser surface texturing based on laser-induced thermal and non-thermal oxidation, and novel technique of magnetic field assisted laser surface texturing.